2014
DOI: 10.1111/sdi.12301
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based Review of Gastrointestinal Bleeding in the Chronic Kidney Disease Patient

Abstract: Patients with end-stage renal disease are more likely to suffer from gastrointestinal (GI) problems, including bleeding from upper and lower sources. Peptic ulcer disease is the most common cause of upper GI bleeding, and although there is some debate in the literature regarding whether the frequency of ulcer disease is higher in patients with kidney disease, it is well established that outcomes are worse in patients with compromised renal function. Angioectasias can be found throughout the GI tract and are an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 43 publications
1
52
0
7
Order By: Relevance
“…[8] The exposure to medications that affects the clotting cascade like anticoagulants, antiplatelets and non-steroidal anti-inflammatory agents (NSAIDS) also place ESRD population at increased risk of UGIB. [4,9] Past studies have demonstrated that in ESRD patients, bleeding from the upper GI tract is more common than from the lower GI tract. [10] Also, gastroduodenal ulcers and erosions are among the frequent causative factors for UGIB in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8] The exposure to medications that affects the clotting cascade like anticoagulants, antiplatelets and non-steroidal anti-inflammatory agents (NSAIDS) also place ESRD population at increased risk of UGIB. [4,9] Past studies have demonstrated that in ESRD patients, bleeding from the upper GI tract is more common than from the lower GI tract. [10] Also, gastroduodenal ulcers and erosions are among the frequent causative factors for UGIB in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Multiple factors have been proposed that increase the risk of UGIB in ESRD patients including platelet dysfunction due to uremia, high prevalence of arteriovenous malformations (AVM), various co-morbidities like cardiovascular disease, diabetes mellitus, liver cirrhosis and old age. [4,[7][8] Anemia has also been suggested to increase the risk of bleeding as red blood cells assist in interface of platelets at the site of injury. The improvement of bleeding time in uremic patients with erythropoietin and blood transfusions also favors this theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with the studies of Aytac et al (26) and Nishikawa et al (23), where renal insufficiency was associated with diverticular rebleeding. Kalman and Pedrosa (38), in their review of gastrointestinal bleeding in CKD patients, stated that this population has an increased risk of gastrointestinal bleeding and that its pathophysiology is often multifactorial. Even though there are no reports in the medical literature specifically linking gastrointestinal bleeding with uremic platelet dysfunction, this is thought to be the major factor that places chronic kidney patients at a higher risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…41 In patients with chronic kidney disease, GI bleeding is also a common complication. 42 Anand et al 43 showed that elevated serum creatinine levels are associated with increased rates of mortality and re-bleeding. We check the performance of 8 prognostic scoring systems in cirrhotic patients with AVB.…”
Section: Articlementioning
confidence: 99%